Pengaruh Motivasi Kerja Dan Kompetensi Terhadap Kinerja Karyawan Pada PT Zahir Internasional Jakarta Selatan - Fatih Muhdi; Andri Priadi; Hamdi Supriadi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of work motivation and competence on employee performance at PT. Zahir Internasional, South Jakarta. The method used is quantitative descriptive research, which is research with data collected through a questionnaire survey and expressed in numerical form involving 80 respondents. Data analysis was performed using simple and multiple linear regression. The results showed that work motivation had a positive and significant effect on employee performance (calculated t = 2.942 > table t = 1.991), meaning that the higher the work motivation, the better the performance. Conversely, competence did not show a significant effect on employee performance (t count = 0.520 < t table = 1.991), indicating that competence did not contribute significantly to performance improvement. Simultaneously, work motivation and competence have a significant effect on employee performance (F count = 4.584 > F table = 3.115), with a total contribution of 10.6%. These findings indicate the importance of increasing work motivation to improve employee performance, while competence needs to be improved to provide more optimal support. This study suggests that companies should pay more attention to motivation and provide appropriate training to improve employee competency, so that organizational performance can be improved.